Pesantren Kilat as a Character-Building Medium Based on Multiple Intelligences at Madrasah Ibtidaiyah Integral Buah Hati Insani, Mataram - Arizka, Rakhmi Vegi (Pendidikan Agama Islam STIT Palapa Nusantara, 2026)
This study is motivated by the limited research on the integration of Multiple Intelligences (MI) theory within short-term Islamic character education programs, despite its importance for holistic learning in faith-based elementary schools. It aims to examine the implementation of an MI-based Pesantren Kilat program, analyze the internalization of Ulil an-Nuha values (piety, wisdom, and social awareness), and evaluate its effectiveness as a medium for character building. Adopting a qualitative design, the research was conducted at Madrasah Ibtidaiyah Integral Buah Hati Insani, Mataram, involving 30 purposively selected participants comprising 4 supervising teachers, 3 program administrators, and 23 students from Grades III, IV, and V. Data were collected through semi-structured interviews, participant observations, and documentation analysis, and were examined using thematic analysis with methodological triangulation to ensure credibility. The findings indicate that structured experiential activities grounded in MI domains, particularly interpersonal, verbal-linguistic, and bodily-kinesthetic intelligences—facilitated active student participation and observable behavioural transformation. The internalization of Ulil an-Nuha values occurred progressively through guided reflection, collaborative engagement, and habituated practice rather than normative instruction alone, demonstrating that character formation is strengthened when cognition, emotion, and action are integrated within meaningful religious experiences. The study concludes that MI-based experiential pedagogy provides an effective framework for holistic character development in short-term Islamic programs and contributes theoretically by linking MI and experiential learning with moral internalization, while offering practical guidance for designing reflective, inclusive character education initiatives. It further recommends that future research examine long-term effects and employ mixed-method approaches across diverse institutional contexts to deepen understanding of MI-based Islamic character education.